Cybersecurity Risks Detection and Prevention (Al-Mansour Journal, 2022)
Cybersecurity is a collection of techniques and processes that are designed for protecting computers, networks, database, and applications from attacks, unauthorized accessing, alteration, or destruction also can be a significant part in the development of information technology as well as Internet services. In Cybersecurity, there are several trends; the biggest one is Web application. Web application is one of the most prevalent platforms for the delivery of information and services via Internet nowadays. Therefore, the importance of web application has increased. At the same time, security risks have also increased. Based on the reports of OWASP (open web application security project), there are ten risks have been listed as the top ten security risks for any web application in the world. SQL injection is one of topmost security risks in OWASP, which is considered in this paper. So securing and maintaining the web application against SQL injection is very hard task and can be classified as a challenge. In this paper, a proposed system works on detecting and preventing SQL injection via using a method named Multi-Connect Architecture (MCA) is presented. The number of queries used in this paper is 130 query. The result of the proposed system is (95%).
Keywords: Cybersecurity; SQL Injection; Detection; Prevention; MCA